Nanoindentation and Microstructure in the Shear Band in a Near Beta Titanium Alloy Ti-5Al-5Mo-5V-1Cr-1Fe - Wang, Bingfeng (Materials (Basel), 2019)
Shear localization is the main deformation mode for the near beta titanium alloy Ti-5Al-5Mo-5V-1Cr-1Fe loaded at high strain rates at either room temperature or cryogenic temperature. Nanoindentation, transmission electron microscopy, and high-resolution electron microscopy technique are applied to character the microstructure features and mechanical properties in the shear band of near beta titanium alloy. A white and straight band is observed in the shear region. Both microhardness and nanoindentaion hardness in the shear region are inferior to those in matrix. The different microstructure in the edge and the center in the shear band contribute to different mechanical properties. The plasticity of the entire shear band is almost homogenous when specimens are deformed at the cryogenic temperature. Rotational dynamic recrystallization is responsible for the formation of the ultrafine grains in the shear band. The edge of the shear band is composed of elongated grains, while there are ultrafine equiaxed grains in the center of the shear band. Deformation temperature has significant influence on the process of the grain refinement and the phase transformation in the shear band (SB). The grain sizes of the shear band in the specimen deformed at room temperature are larger than those in the specimens deformed at cryogenic temperature. The shear band consists of α phase grains in the specimen deformed at room temperature, and the shear band consists of α phase and lath-like α′ phase grains in the specimen deformed at cryogenic temperature. Finally, the mechanisms for phase transformation in the shear band are illustrated.